Key Matrix Proteins Within the Pancreatic Islet Basement Membrane Are Differentially Digested During Human Islet Isolation. Issue 2 (6th September 2016) - Cross, S. E.; Vaughan, R. H.; Willcox, A. J.; McBride, A. J.; Abraham, A. A.; Han, B.; Johnson, J. D.; Maillard, E.; Bateman, P. A.; Ramracheya, R. D.; Rorsman, P.; Kadler, K. E.; et al.
Abstract : Clinical islet transplantation achieves insulin independence in selected patients, yet current methods for extracting islets from their surrounding pancreatic matrix are suboptimal. The islet basement membrane (BM) influences islet function and survival and is a critical marker of islet integrity following rodent islet isolation. No studies have investigated the impact of islet isolation on BM integrity in human islets, which have a unique duplex structure. To address this, samples were taken from 27 clinical human islet isolations (donor age 41–59, BMI 26–38, cold ischemic time < 10 h). Collagen IV, pan‐laminin, perlecan and laminin‐α5 in the islet BM were significantly digested by enzyme treatment. In isolated islets, laminin‐α5 (found in both layers of the duplex BM) and perlecan were lost entirely, with no restoration evident during culture. Collagen IV and pan‐laminin were present in the disorganized BM of isolated islets, yet a significant reduction in pan‐laminin was seen during the initial 24 h culture period. Islet cytotoxicity increased during culture. Therefore, the human islet BM is substantially disrupted during the islet isolation procedure. Islet function and survival may be compromised as a consequence of an incomplete islet BM, which has implications for islet survival and transplanted graft longevity. Abstract : This study characterizes the human islet basement membrane before and after islet isolation, demonstrating that substantial disruption of both layers of the duplex basement membrane occurs during the procedure, potentially compromising islet survival.